Blacking Up : Une histoire du rock au prisme du blackface - Keivan Djavadzadeh (Transatlantica)
Blackface minstrelsy is a form of popular American theater that gained popularity in the first half of the 19th century. As a form of theatrical makeup, blackface consisted of mostly white performers using burnt cork to blacken their skin. If the blackface makeup practice faded away in the 1950s, the reality behind it has carried on since. On the basis of an analysis of rock music, its origins and its transatlantic circulations, I will examine the racial politics of popular music and postulate a continuity of the blackface cycle. I intend to show that what has been integrated with the commercialization of black music is black culture more than Black people themselves. Thus, White artists, such as Elvis Presley or Mick Jagger, have worn a metaphorical blackface mask while “borrowing” signs from the African-American tradition. But some Black artists who were “rediscovered” in the 1960s (Blues Revival) also had to entertain their White audience with the thrill of a so-called “racial authenticity.”